Low-Load Blood-flow Restriction Training for Medial Tibial Stress-Syndrome in Athletes: A Case Series - Anders F. Brekke; Johanne Bjørklund; Rosa C. Holse; Christian Larsen; Mikkel H. Hjortshoej (International Journal of Sports Physical Therapy)
# Background